?-solanine and ?-chaconine from Potato (Solanum tuberosum) for Endometrial Cancer Therapy: In silico Study - Krisnamurti, Gabriella Chandrakirana; Wulansari, Shinta; Sari, Dewi Ratih Tirto (Proceeding International Conference on Religion, Science and Education, 2022)
The study aims to identify the potency of ?-solanine and ?-chaconine in endometrium cancer. Whether it could increase the cancer risk or be an anti-cancer agent. The ?-solanine (CID9549171), ?-chaconine (CID442971), and cordycepin (CID452851) structures were generated from MolView by inputting the SMILES from PubChem of each compound. The 3D structure of adenosine (CID60961) was downloaded from PubChem. Adenosine A2 Receptor (A2AR) (2YDO) as a macromolecule was downloaded from PDB. Protein and ligands were docked using Molegro Virtual Docker 5. The docking results were analyzed using Pymol and Discovery studio 21.1.1 and visualized in 2D and 3D visualization. The ?-solanine and ?-chaconine were predicted for their pharesiamacological effect using PASS Online. The result showed that ?-solanine and ?-chaconine were able to bind to A2AR active sites. The amino acid residues involved in the ?-solanine and ?-chaconine binding with A2AR were identical. Interestingly, the result showed that ?-solanine can behave like cordycepin when it interacts with A2AR. The binding site of cordycepin – A2AR is most likely similar to ?-solanine – A2AR complex. It could be assumed that ?-solanine has similar potency with cordycepin as anti-cancer. In addition, the pharmaceutical prediction of ?-solanine and ?-chaconine showed the potency as anti-cancer for both compounds. This study predicted that ?-solanine and ?-chaconine, which are known as toxic, could be anti-cancer agents. The ?-solanine could work in a similar mechanism as cordycepin, whereas the ?-chaconine mechanism as anti-cancer needs further identification.